2020
DOI: 10.1371/journal.pone.0239673
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput, image-based phenotyping reveals nutrient-dependent growth facilitation in a grass-legume mixture

Abstract: This study used high throughput, image-based phenotyping (HTP) to distinguish growth patterns, detect facilitation and interpret variations to nutrient uptake in a model mixed-pasture system in response to factorial low and high nitrogen (N) and phosphorus (P) application. HTP has not previously been used to examine pasture species in mixture. We used redgreen-blue (RGB) imaging to obtain smoothed projected shoot area (sPSA) to predict absolute growth (AG) up to 70 days after planting (sPSA, DAP 70), to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Similar studies on legume and non-legume mixtures had attributed high values of relative yields total through the use of different nitrogen sources in addition to differences in root and aboveground characteristics (Zand and Beckie 2002;Ball et al 2020). Contrary to their study, the results of this study showed a lower value of relative yield totals through the use of water stress as the main factor in addition to above-ground biomass.…”
Section: Relative Competitive Abilitymentioning
confidence: 71%
“…Similar studies on legume and non-legume mixtures had attributed high values of relative yields total through the use of different nitrogen sources in addition to differences in root and aboveground characteristics (Zand and Beckie 2002;Ball et al 2020). Contrary to their study, the results of this study showed a lower value of relative yield totals through the use of water stress as the main factor in addition to above-ground biomass.…”
Section: Relative Competitive Abilitymentioning
confidence: 71%
“…As anticipated, the faster-growing, more nutrient-acquisitive grass species responded positively to N addition, and when cultivated with a legume; the slower-growing, more nutrient-homeostatic legume species responded positively to P addition and growth in mixture. Moreover, the grass had a faster relative growth rate than the legume, and this effect was augmented in mixed cultivation (Ball et al, 2020). It is important to note that enhanced growth of grass under N addition in mixture may be attributed to a greater availability of N for two, versus four, grass plants and thus may not be due to facilitation.…”
Section: Discussionmentioning
confidence: 98%
“…Our experiment was conducted from the 28 th of October 2018 in a greenhouse maintaining natural average temperatures of 27°C/16°C on a day/night cycle and an average day length between 07:00 -19:00 under natural light, for 70 days (Ball et al, 2020). The 70-day growth cycle was chosen to capture the ideal temperature range for germinating and growing both species while avoiding potential for summer dormancy with increasing temperatures (Brar et al, 1991;Watson et al, 2000).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be facilitative (positive) or competitive (negative). In grasslands, legumes often facilitate grasses through N-fixation, which increases ecosystem productivity (Ball et al, 2020), in return for improved microclimatic conditions such as wind protection (Walker et al, 2003). Conversely, fast-growing dominant grasses often compete with one another for limited resources, which can result in productivity loss (Corbin & D'Antonio, 2004;Fay et al, 2003).…”
Section: Introductionmentioning
confidence: 99%